Maksimalisasi Mahāratul Kitābah Melalui Pengaruh Kaligrafi - Bella Tiara Putri; Devi Khumaira Hayati; Ashrafah Alaifhi Aulia; Mutia Zahara; Sahkholid Nasution (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Arabic is a language that has its own characteristics from other languages, both in terms of pronunciation and writing. For some people who have high artistic value towards something, Arabic can be a truly extraordinary work of art, therefore one of the methods used to improve or maximize the Maharatul Kitabah is through the influence of calligraphy. The research method used is a qualitative method and literature review sourced from books, articles, journals. The aim of this research is the importance of maximizing calligraphy in improving maharatul kitabah (writing ability) in Arabic. The results of this research are to improve the ability to write (maharatul kitabah) in Arabic script, as well as to beautify the way of writing Arabic letters by studying calligraphy. As is known, calligraphy is the art of beautiful writing. By studying calligraphy, you can easily improve your Arabic writing to be better and in accordance with the rules of Arabic writing. The types of calligraphy writing that the research includes are types of calligraphy that are very frequently used and do not depart from the rules of actual Arabic writing. If the art of calligraphy writing does not comply with the rules of original Arabic writing then the purity of the writing will be damaged.